Digital Banking Satisfaction: A SeaBank Study using The End User Computing Satisfaction (EUCS) Model - Oktoriani, Della; Rahmawita, Medyantiwi; Ahsyar, Tengku Khairil; Syaifullah, Syaifullah (Universitas Hamzanwadi, 2025)
SeaBank serves as a digital banking platform that enables users to conduct financial transactions conveniently via their smartphones. Despite its widespread adoption, concerns regarding service quality persist. The objective of this study is to assess user satisfaction with the SeaBank application using the EUCS model. This research employs a quantitative methodology with PLS-SEM as the analytical technique to examine variable relationships. The software used for data analysis is SmartPLS 4. Data were collected through an online survey comprising 23 items, involving 100 active users aged 17 and above. Model evaluation includes both outer model and inner model analyses to ensure construct validity and reliability. The findings indicate that content, accuracy, and ease of use have a significant and positive impact on user satisfaction. Conversely, format and timeliness do not have a significant influence, suggesting that these aspects play a marginal role in shaping users' overall perception of the application. Implications of this study highlight the necessity of improving information quality, data accuracy, and intuitive interface design to enhance user satisfaction. While enhancements to format and timeliness can be considered, they are not a primary focus. This research provides valuable insights for application developers in designing user-centered service improvement strategies.